Adsorption Of Basic Dye (Methylene Blue) On Corn Cob Based Activated Carbon (CCAC) : Equilibrium, Kinetic And Thermodynamic Studies - Ahmad Rasidi, Ahmad Arif Aiman (Universiti Sains Malaysia, 2018)
In this study, the corn cob based activated carbon (CCAC) prepared by physical activation using microwave radiation as a heating source was derived from agricultural waste and its adsorption performance in the removal of methylene blue (MB) from an aqueous solution was analyzed in a batch system. The optimum preparation conditions were obtained at radiation power of 400 W and activation time of 4 minutes which resulted with CCAC of BET surface area, mesopore surface area, total pore volume and percentage of fixed carbon of 604.6m2/g, 458.32m2/g, 0.4557cm3/g and 66.84%, respectively. The obtained average pore diameter of the CCAC (5.45nm) lies within the range of mesoporous region which is in between 2nm to 50nm. The factors that influence the adsorption of MB onto CCAC such as contact time (0-24hours), initial dye concentration (25mg/L-300mg/L) and solution temperature (30'C-60'C) were evaluated. The result showed that the adsorption uptake was found to increase with an increase in contact time, initial dye concentration and solution temperature. The equilibrium data were evaluated using Langmuir, Freundlich and Temkin isotherms while pseudo-first order and pseudo-second order kinetic models were applied to test the experimental data. The Freundlich isotherm and pseudo-second order kinetic model were best describes the MB adsorption onto the CCAC. Thermodynamic studies were carried out to determine the thermodynamic parameters such as Gibbs free energy (ΔG), enthalpy (ΔH) and entropy (ΔS).From the studies, it was found that the MB adsorption on CCAC was physisorption process, spontaneous and endothermic in nature.